(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2008)
The results of the quantitative metal analysis of the environmental samples associated with electronic wastes processing in China and India were obtained. High levels of toxic metals which known to have extensive use in the electronics sector were found around workplaces, surrounding soils and water courses. Extremely high levels of lead, tin, copper and cadmium were registered. The levels of barium, chromium, cobalt, gold, mercury, nickel, silver and zinc were also relatively abundant in many samples.